Bacteroides vulgatus alleviates dextran sodium sulfate-induced colitis and depression-like behaviour by facilitating gut-brain axis balance - Xing Wu; Xing Wu; Jiahao Xu; Jiahao Xu; Jingbo Li; Minzi Deng; Zhaohua Shen; Kai Nie; Weiwei Luo; Weiwei Luo; Chao Zhang; Chao Zhang; et al. (Frontiers in Microbiology, 2023)
BackgroundPatients with inflammatory bowel disease (IBD) have a higher prevalence of depression. Gut microbiota dysbiosis plays an important role in IBD and depression. However, few studies have explored the characteristic microbiota of patients with IBD and depression (IBDD), or their role in IBDD.MethodsWe performed deep metagenomic sequencing and 16S rDNA quantitative PCR to characterise the gut microbial communities of patients with IBDD and patients with IBD without depression (IBDND). We then assessed the effect of the microbiota on colitis and depression in mouse models of dextran sulfate sodium salt (DSS)-induced colitis and lipopolysaccharide (LPS)-induced depression. Furthermore, liquid chromatography–tandem mass spectrometry was used to analyse the microbiota-derived metabolites involved in gut–brain communication. Evans Blue tracer dye was used to assess blood–brain barrier (BBB) permeability.ResultsOur results showed that the faecal abundance of Bacteroides vulgatus (B. vulgatus) was lower in patients with IBDD than in those with IBDND. In the DSS-induced colitis mouse model, the B. vulgatus group showed a significantly lower disease activity index score, lesser weight loss, and longer colon length than the DSS group. Moreover, B. vulgatus relieved depression-like behaviour in the DSS-induced colitis mouse model and in the LPS-induced depression mouse model. Furthermore, the key metabolite of B. vulgatus was p-hydroxyphenylacetic acid (4-HPAA), which was found to relieve intestinal inflammation and alleviate depression-like behaviours in mouse models. By increasing the expression of the tight junction protein claudin-5 in the vascular endothelium of the BBB, B. vulgatus and 4-HPAA play critical roles in gut–brain communication.ConclusionB. vulgatus and B. vulgatus-derived 4-HPAA ameliorated intestinal inflammation and relieved depressive symptoms through the gut–brain axis. Thus, administration of B. vulgatus or 4-HPAA supplementation is a promising therapeutic strategy for treating IBD, particularly IBDD.